2016
DOI: 10.3389/fnhum.2016.00539
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Automation Triggered by EEG-Based Mental Workload Index: A Passive Brain-Computer Interface Application in Realistic Air Traffic Control Environment

Abstract: Adaptive Automation (AA) is a promising approach to keep the task workload demand within appropriate levels in order to avoid both the under- and over-load conditions, hence enhancing the overall performance and safety of the human-machine system. The main issue on the use of AA is how to trigger the AA solutions without affecting the operative task. In this regard, passive Brain-Computer Interface (pBCI) systems are a good candidate to activate automation, since they are able to gather information about the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 60 publications
1
153
0
Order By: Relevance
“…For instance, Prinzel et al (2000) utilized the continuous monitoring of brain waves that could be used to drive the level of automation and optimize the user's level of task engagement. Similarly, some authors managed to optimize air traffic controllers' task demand by triggering different levels of assistance (Aricò et al, 2016;Di Flumeri et al, 2019). These latter studies reported better human performance when neuro-adaptive automation was switched on compared to other conditions.…”
Section: Task and Automation Adaptationmentioning
confidence: 99%
“…For instance, Prinzel et al (2000) utilized the continuous monitoring of brain waves that could be used to drive the level of automation and optimize the user's level of task engagement. Similarly, some authors managed to optimize air traffic controllers' task demand by triggering different levels of assistance (Aricò et al, 2016;Di Flumeri et al, 2019). These latter studies reported better human performance when neuro-adaptive automation was switched on compared to other conditions.…”
Section: Task and Automation Adaptationmentioning
confidence: 99%
“…Nowadays, many occupations require high levels of vigilance, for example, security personnel [10], employees tasked with monitoring surveillance cameras or baggage screening experts [11], driving vehicles [12], diagnostic medical screening [13], real classroom settings [14], and industrial and air traffic control [15][16][17]. The need to remain alert and situation-aware, and to detect infrequent but critical signals is crucial in a lot of job occupations: A vigilance failure in any of these domains could have dramatic impacts.…”
Section: Current Key Research Points On Vigilancementioning
confidence: 99%
“…A Stepwise Linear Discriminant Analysis (SWLDA) was utilized for reducing the dimensionality of the feature space to avoid over-training by selecting features that offer the highest independent discriminative information. SWLDA has been widely used for feature selection in brain-computer interfaces and EEG-based affective state classification [Aricò et al 2016;Berka et al 2007]. It is a numerical approach that iteratively adds/removes features with significant/insignificant discrimination effect.…”
Section: Feature Selection and Classificationmentioning
confidence: 99%